A classe hospitalar sob o olhar de professores de um hospital público infantil - Carvalho, Ana Rosa Rebelo Ferreira de (2008)
This aim of this study was to understand the significance that teachers in a Hospital Class, at a children's hospital in São Paulo, give to their work. The term Hospital Class is recognized by the Ministry of Education and Sport s (MEC/ SEESP) Bureau for Special Education, and refers to pedagogic-educational care for children and young people, which takes place in health-care environments, whether in cases of hospitalization, daily or weekly outpatient services or full mental health treatment. Three teachers who have worked in Hospital Classes at a public children s hospital for at least a year took place in this research. Data were collected through semistructured interviews and analyzed from a qualitative approach perspective, by analyzing content. Data was collected at the hospital at a time and place chosen by the participants. After examining the data and the purpose of the study, three main themes were identified: the importance that the participants attach to their work; prospects for the future of the participants, and the participants educational background. The analysis showed that the teachers believe their work has a role that goes beyond that of a mere teacher. However, the participants reported feeling satisfied and recognized for the duties they perform, despite finding it difficult to cope with the socioeconomic status of patients and with possible deaths. The deaths of child patients affect their professional, personal and family lives, which probably occurs because of the lack of specific training, interdisciplinary work and psychological support. The results demonstrate that there is a need for specific preparation for working in a hospital environment and such individuals should be included in the health care team